Strategi Manajemen Relawan Berbasis Kesejahteraan dan Keterlibatan untuk Membangun Loyalitas Relawan Bankziska - Ni'matul Fitria Mukaromah; Iza Hanifuddin; Amin Wahyudi; Faruq Ahmad Futaqi (Journal of Economics, Law, and Humanities, 2025)
This study aims to analyze the strategies implemented by Bankziska Lazismu in building volunteer loyalty, to identify the underlying factors behind these strategies, and to examine their impact on volunteer commitment. This phenomenon is noteworthy as it reveals a group of individuals willing to contribute without financial compensation yet remain highly motivated and dedicated to their service. The research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews with managers, staff, and volunteers of Bankziska Lazismu and through documentation studies. Data analysis was conducted inductively to identify strategic patterns that emerged empirically in the field. The findings indicate that Bankziska Lazismu applies welfare-based and engagement-oriented strategies to enhance volunteer loyalty. This is reflected in providing incentives, welfare programs, gifts, and various forms of appreciation. Furthermore, the organization strengthens loyalty through intensive communication, volunteer involvement in institutional activities, and capacity-building training programs. However, the implementation of some strategies remains suboptimal, such as family gatherings, continuous training, and the provision of supporting facilities. Therefore, optimizing the implementation of these strategies is necessary to strengthen volunteer loyalty more effectively and sustainably.